(untitled) (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-4-37-49 The cognitive approach to the analysis of the lexical meaning of words makes it possible to explain the complex semantic structures of linguistic units by means of identifying cognitive models and mechanisms. These cognitive constructs underlie the formation of both literary and non-literary meanings of words. Somatic vocabulary, i. e. words naming parts of the human body, is of particular interest to cognitive linguists, as it clearly demonstrates the effect of one of the main postulates of cognitive linguistics, the postulate of embodied mind. Moreover, the physical, structural and functional properties of body parts also have a potential in forming the semantics conceptualisation of the lexemes. The data obtained from BNC of the lexeme mouth, 500 citations, give the following results. The research shows that the literal meaning of the lexeme mouth is based on its perception as a container (MOUTH AS A CONTAINER), as a static object and as an object with inherent physiological properties (MOUTH AS A OBJECT (STATIC PHYSIOLOGICAL)). The collocations of mouth in that meaning is limited to a certain group of prepositions, verbs and adjectives. In some cases the literal meaning has a strong symbolic connotation which is easily inferred. The connotations reflect positive and negative feelings and states of a person. This fact confirms the thesis about the close interrelation of the internal state of a person and its external physiological manifestations. We single out positive and negative semantic prosody of these citations, such as firmness, attractiveness, anger, irritation, etc. The non-literal metonymic meaning of mouth gives evidence of the models MOUTH FOR ITS PARTS, MOUTH FOR A PERSON, MOUTH FOR ACTIVITY with their sub-models. The metonymic relations between the two concepts of each model are connected by contiguity, as both concepts are located inside one specific idealized cognitive model describing mouth as a body part, a person and human activities. Key words: cognitive linguistics, embodied mind, somatic vocabulary, cognitive semantics, cognitive metonymy, cognitive metaphor